Market segmentation and perceived value in the gastronomy industry of Medellin, Colombia: an empirical study - Casadiego-Alzate, Rodolfo; Balzan, Alexander; Castañeda-Quirama, Tatiana; Velásquez-Calle, Paula Andrea (Revista Venezolana de Gerencia, 2025)
This study examines market segmentation within the gastronomic industry in Medellín, Colombia, focusing on perceived value, consumer types, and brand positioning among young adults. Using a mixed-method approach with a sequential exploratory design, focus groups were conducted to identify key attributes valued by consumers. This data was the base for a subsequent quantitative survey, which delineated three distinct market segments characterized by their preferences for connectivity, cleanliness, reasonable prices, ambiance, quality of service, variety in dishes, portion size, and service time. The results suggest that young adults in Medellín prioritize a combination of quality and experience factors in their gastronomic choices. The conclusions highlight sociodemographic differences, such as the tendency of women to seek information about establishments before visiting the establishments or the preference of middle-class youth for casual dining restaurants, results that contribute to marketing management and tourism decision-making.